Goiter Prevalence and Associated Factors among Women in Hargeisa, Somalila - Dahir, Shukri Mohamed; Mohamed, Afnan Abdirahman; H Hassan, Hassan Jama; Sonmez, Recep Ercin; Ozsoy, Mehmet Sait; Kiruja, Jonah; Alimoglu, Orhan (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Goiter, which is associated with various risk factors, is highly prevalent in Hargeisa region of Somalia and is a serious health problem among women living in the region. Objective: This study aims to reveal the true extent of the problem, identify the causative factors and suggest preventive methods accordingly. Methods: A cross-sectional analysis was conducted on 270 female patients randomly selected from 1659 patients at Hargeisa Group Hospital (HGH), in Somalia, between January and August of 2022. The study sample was equally distributed between those with and without a diagnosis of goiter. Independent risk factors were identified by making comparisons between groups. Results: For the study group, dietary habits were identified as an important risk factor for the development of goiter. Patients who regularly consumed ‘cabbage’ - 188 (87.4%) had a higher rate of goiter compared to those who did not - 64 (47.4%); (p<0.001). Furthermore, those who consumed iodized salt regularly or more frequently - 54 (40%) were less likely to have goiter compared to those who did not - 128 (94.8%); (p<0.001). The use of non-iodized salt and cabbage consumption were identified as predictive factors for the development of goiter. Conclusion: Randomized studies with larger study groups should be conducted. The Minister of Health, health professionals and the media should work in cooperation to raise public awareness and take necessary precautions. International Journal of Human and Health Sciences Vol. 08 No. 02 Apr’24 Page: 192-197